The mitochondrial permeability transition pore: a mystery solved? - Bernardi, Paolo (Frontiers in Physiology, 2013)
The permeability transition denotes an increase of the mitochondrial inner membrane permeability to solutes with molecular masses up to about 1,500 Da. It is presumed to be mediated by opening of a channel, the permeability transition pore (PTP), whose molecular nature remains a mystery. Here I briefly review the history of the PTP, discuss existing models, and present our new results indicating that reconstituted dimers of the FOF1 ATP synthase form a channel with properties identical to those of the mitochondrial megachannel, the electrophysiological equivalent of the PTP. Open questions remain, but there is now promise that the PTP can be studied by genetic methods to solve the large number of outstanding problems.